Urinary tissue inhibitor of metalloproteinase-2 as an early predictor for acute kidney injury in critically ill children - Abouhadid, Maha A.; Abdel Gawad, Tarek A.; El Gebaly, Howida H.; Abdallah, Azza A.; El Refay, Amira S.; Helmy, Neveen M.; Allam, Ahmad M. (International Journal of Health Sciences, 2023)
Objectives: Acute kidney injury (AKI) is one of the most devastating complications of critical illness in children. Serum creatinine (Scr) is considered the gold standard for AKI diagnosis yet noted to be late and inaccurate. This raises the need for an early and accurate biochemical parameter for the early detection of AKI. This research aimed to explore the role of urinary tissue inhibitor metalloproteinase 2 (TIMP-2) in the early prediction of AKI, compared to standard biomarkers, in critically ill children admitted to pediatric intensive care unit (PICU). Urine TIMP2 was previously explored in multiple adult studies and showed promising results; however, the study of its role in pediatric population was limited. Methods: This study was a prospective cohort study including 42 critically ill children who are at increased risk of AKI. Cases were recruited from the PICU in the Children’s Hospital of Ain-Shams University, Cairo – Egypt over 10 months’ duration. Urine samples were collected to measure urinary TIMP-2 and blood samples were taken to measure the levels of Scr, creatinine clearance, and blood urea nitrogen. Urine output in 24 h was also calculated. Results: Urinary TIMP-2 showed considerably higher levels in AKI compared to non-AKI patients as early as day 1, whereas increased levels of Scr and decreased urine output were noticed later (day 3 and day 5, respectively). A notable correlation existed between TIMP-2 at day 1 and creatinine at day 3. Conclusion: The present study revealed that urinary TIMP-2 could have an important role in the early prediction of AKI before the increase in Scr and more deterioration in kidney functions.